Stylistics of Syntactic and Morphological Structures in the Qur’anic Pause:A Descriptive Analytical Study of Surah Al-Israʾ as a Model (Journal of the College of Basic Education, 2026)
The miraculous nature of the Holy Qur’an manifests in various dimensions, most notably its rhetorical, numerical, and linguistic inimitability—encompassing syntax, morphology, semantics, structure, and phonology. These aspects collectively give rise to stylistic phenomena that merit in-depth scholarly investigation. This study focuses on the Qur’anic pause (al-fāṣilah) as a linguistic system imbued with a multitude of stylistic features. It specifically explores the syntactic and morphological aspects of the pauses in Surah Al-Israʾ, chosen for its diverse patterns of terminal pauses and the predominant occurrence of the open /aː/ vowel sound at the end of most verses, whether in their absolute or accusative forms.The research aims to examine the aesthetic dimensions of these phonological structures and their semantic implications within syntactic constructions, thereby uncovering the role they play in conveying meaning and enriching interpretation. Given that the pauses in this surah involve a variety of syntactic themes and morphological structures, they contribute significantly to the phonological and semantic layers of the text. This linguistic richness is explored through a descriptive and analytical methodology, highlighting the synergistic role of syntax and morphology in enhancing meaning and contributing to the surah’s overarching message